Cannabis use and posttraumatic stress disorder: prospective evidence from a longitudinal study of veterans. Issue 3 (17th February 2022) - Metrik, Jane; Stevens, Angela K.; Gunn, Rachel L.; Borsari, Brian; Jackson, Kristina M.
Abstract: Background: Posttraumatic stress disorder (PTSD) is the most highly co-occurring psychiatric disorder among veterans with cannabis use disorder (CUD). Despite some evidence that cannabis use prospectively exacerbates the course of PTSD, which in turn increases the risk for CUD, the causal nature of the relationship between cannabis and psychiatric comorbidity is debated. The longitudinal relationship between PTSD diagnosis and traumatic intrusion symptoms with cannabis use and CUD was examined using cross-lagged panel model (CLPM) analysis. Methods: Prospective data from a longitudinal observational study of 361 veterans deployed post-9/11/2001 included PTSD and CUD diagnoses, cannabis use, and PTSD-related traumatic intrusion symptoms from the Inventory of Depression and Anxiety Symptoms. Results: A random intercept CLPM analysis that leveraged three waves (baseline, 6 months and 12 months) of cannabis use and PTSD-related intrusion symptoms to account for between-person differences found that baseline cannabis use was significantly positively associated with 6-month intrusion symptoms; the converse association was significant but reduced in magnitude (baseline use to 6-month intrusions: β = 0.46, 95% CI 0.155–0.765; baseline intrusions to 6-month use: β = 0.22, 95% CI −0.003 to 0.444). Results from the two-wave CLPM reveal a significant effect from baseline PTSD to 12-month CUD ( β = 0.15, 95% CI 0.028–0.272) but not from baseline CUD to 12-month PTSD ( β = 0.12, 95% CI −0.022 to 0.262). Conclusions: Strong prospective associations capturing within-person changes suggest that cannabis use is linked with greater severity of trauma-related intrusion symptoms over time. A strong person-level directional association between PTSD and CUD was evident. Findings have significant clinical implications for the long-term effects of cannabis use among individuals with PTSD.